2018
DOI: 10.3390/su10061930
|View full text |Cite
|
Sign up to set email alerts
|

Employee Fitness Programs: Exploring Relationships between Perceived Organizational Support toward Employee Fitness and Organizational Sustainability Performance

Abstract: This study investigates the influence of employee fitness programs on organizational sustainability performance from the perspective of organizational support as perceived by employees. Organizational sustainability performance was specified as a second-order factor, which was affected by three first-order factors: financial performance, social performance, and environmental performance. A snowball sampling method was employed to conduct an online survey of working adults in Shanghai to test the proposed hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
0
12
1
Order By: Relevance
“…Companies' wellness programs were measured using a 13-item scale adapted from Wang et al. (2018) and Sonnentag and Pundt (2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Companies' wellness programs were measured using a 13-item scale adapted from Wang et al. (2018) and Sonnentag and Pundt (2016).…”
Section: Methodsmentioning
confidence: 99%
“…If employees perceive that their efforts are recognized by the company, they are likely to develop productive attitudes and carry out their tasks in a highly productive manner (Tsai, 2013). Wang et al (2018) indicate that POS leads employees toward achieving organizational goals, enabling them to become emotionally attached to the company. POS would thus manifest itself in a positive feeling for an employee with regard to their work environment, reducing stress levels and giving him or her the opportunity to develop further creative behaviors (Eisenberger et al, 1986).…”
Section: Pos and Employee Innovative Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Although financial performance is still the main goal of many organizations, they are beginning to study and implement practices on sustainable development (Afzal et al, 2017). Researchers (Esteves et al, 2012;Lawler & Worley, 2012;Istrate et al, 2017;Batista & Francisco, 2018;Wang et al, 2018;Lueg et al, 2019;Barbosa et al, 2020;Ren & Jackson, 2020;Xu et al, 2020;Nader et al, 2022) demonstrated that in order to ensure market competitiveness and corporate reputation, organizations need to implement triple sustainability practices: economic, environmental and social improvement practices. These practices must be analyzed according to the organization size, to the level of business maturity, strategic planning and organizational structure (Batista & Francisco, 2018).…”
Section: Figure No 6 -Citations Of Articles Under Analysismentioning
confidence: 99%
“…It is crucial to understand that employees are the most important stakeholders in any improvement initiative aimed at improving business performance (Škerlavaj et al, 2007). In practice, organizations should promote perceived organizational support and other related mechanisms to maintain employee engagement (Albalawi et al, 2019) and achieve the desired level of sustainability performance (Wang et al, 2018). As such, it is necessary to focus on intangible resources, such as employee involvement and engagement in sustainability initiatives, that can lead to higher job satisfaction and better performance results.…”
Section: Sustainability Innovation Practicesmentioning
confidence: 99%